Automatic proof-search heuristics in the Maude invariant analyzer tool (2013)
The Invariant Analyzer Tool is an interactive tool that mechanizes an inference system for proving safety properties of concurrent systems, which may be infinite-state or whose set of initial states may be infinite. This paper presents the automatic proof-search heuristics at the core of the Maude Invariant Analyzer Tool, which provide a substantial degree of automation and can automatically discharge many proof obligations without user intervention. These heuristics can take advantage of equationally defined equality predicates and include rewriting, narrowing, and SMT-based proof-search techniques.